2021
DOI: 10.1093/bioinformatics/btab777
|View full text |Cite
|
Sign up to set email alerts
|

Seq-SetNet: directly exploiting multiple sequence alignment for protein secondary structure prediction

Abstract: Motivation Accurate prediction of protein structure relies heavily on exploiting multiple sequence alignment (MSA) for residue mutations and correlations as this information specifies protein tertiary structure. The widely used prediction approaches usually transform MSA into inter-mediate models, say position-specific scoring matrix or profile hidden Markov model. These inter-mediate models, however, cannot fully represent residue mutations and correlations carried by MSA; hence, an effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…AlphaFold has successfully used MSA instead of sequence profiles to produce accurate structure prediction. Another study by Ju et al [163] suggested the use of MSA as a direct input for the PSSP model concerning that sequence profiles derived from MSA (PSSM and HMM profiles) may not be able to represent residue mutations and correlations. The model, called Seq-SetNet, performed two stages, encoding and aggregation, to deduce the structural properties of each amino acid in the input sequence.…”
Section: Pssp In Post-alphafold Publicationmentioning
confidence: 99%
“…AlphaFold has successfully used MSA instead of sequence profiles to produce accurate structure prediction. Another study by Ju et al [163] suggested the use of MSA as a direct input for the PSSP model concerning that sequence profiles derived from MSA (PSSM and HMM profiles) may not be able to represent residue mutations and correlations. The model, called Seq-SetNet, performed two stages, encoding and aggregation, to deduce the structural properties of each amino acid in the input sequence.…”
Section: Pssp In Post-alphafold Publicationmentioning
confidence: 99%